Nursing Lecturers’ Readiness to Teach Online in the ‘New Normal’ Post COVID-19 Era - Pramusita, Santa Maya; Sihombing, Riama Marlyn; Situmorang, Komilie (Universitas Aisyah Pringsewu, 2022)
Introduction – As a way of reducing Covid-19’s infection rate, Indonesian students, and teachers at all levels of education are forced to undergo online teaching and learning, without much preparation. This also applies to nursing lecturers of associate degree nursing programs (D3). Purpose – This study attempts to find out the readiness of lecturers D3 nursing program to teach fully remote after this pandemic end, and the most associated variable on D3 nursing lecturers’ readiness. This is done to anticipate if full online teaching method is still applied by stakeholders in the ‘new normal era. Methodology – Inferential quantitative with a cross-sectional approach was utilized. The population encompassed 344 actively working lecturers in private institutions of DKI Jakarta and Banten. The sample in this study was taken using an accidental sampling technique, and the data were gained using a Likert-scale questionnaire. This study was analyzed using the Chi-square test. Findings – The results showed that half of the respondents (55.4%) had low readiness. Furthermore, there was a significant correlation between education (p=0.023). These results can be a basis for making recommendations in support of policies and decisions concerning the implementation of online learning. Abstrak: Pendahuluan – Sebagai upaya menekan angka penularan Covid-19, siswa dan pengajar di semua jenjang pendidikan Indonesia diminta menjalani kegiatan belajar mengajar secara daring, tanpa banyak persiapan. Demikian pula dosen pada program studi D3 Keperawatan. Tujuan – Penelitian ini bertujuan untuk mengetahui kesiapan dosen D3 keperawatan untuk mengajar daring secara sepenuh setelah pandemi berakhir, dan variabel yang berhubungan dengan kesiapan dosen. Hal ini dilakukan untuk mengantisipasi jika metode pengajaran daring masih diterapkan oleh para pemangku kepentingan di era kenormalan baru. Metodologi – kuantitatif inferensial dengan pendekatan cross-sectional. Populasi pada penelitian ini adalah 344 dosen aktif yang bekerja di instansi swasta sekitaran DKI Jakarta dan Banten. Sampel diambil menggunakan teknik accidental sampling, dan data dikumpulkan menggunakan kuesioner skala likert. Data kemudian dianalisis menggunakan chi square. Temuan – Hasil penelitian menunjukkan bahwa setengah dari responden (55,4%) memiliki kesiapan yang rendah. Selanjutnya, terdapat hubungan yang signifikan antara pendidikan (p=0,023). Hasil ini dapat dijadikan dasar untuk membuat rekomendasi dalam mendukung kebijakan dan keputusan terkait pelaksanaan pembelajaran daring